Collodion Baby And Cholestasis: A Rare Case Report - Bagus Setyoboedi; Rendi Aji Prihaningtyas; Syania Mega Octariyandra (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2024)
Collodion baby with cholestasis is an uncommon condition. The term "collodion baby" refers to newborns with thick skin covering their entire body. Neonatal cholestasis is a form of conjugated cholestasis hyperbilirubinemia caused by reduced bile flow. The condition causes persistent jaundice (over two weeks) and elevated conjugated bilirubin. Genetic abnormalities or gene mutations have been reported in neonatal ichthyosis syndrome with cholestasis. A case report of a collodion baby, a rare congenital condition characterized by a parchment-like membrane covering the entire body, was brought to Dr. Soetomo General Academic Hospital. Prolonged jaundice was one of the other findings. A skin biopsy found characteristics consistent with the diagnosis of collodion in a newborn. The paediatric team managed this case, which was treated in collaboration with a dermatologist. This case showed that newborn collodion syndrome required skin care, cholestasis screening, and jaundice management from birth.